Histopathology and immune histochemistry of red tattoo reactions. Issue 4 (29th May 2015) - Høgsberg, T.; Thomsen, B. M.; Serup, J.
<x xml:space="preserve">Abstract</x> Background The majority of tattoo reactions are affiliated to red pigmented areas and often suspected to be allergic in nature. A sizeable series of biopsies of such reactions has not previously been performed. The aim of this study was to type and grade epidermal and dermal changes in tattoo reactions to red/red nuances by microscopy and immunochemistry relevant for the assessment of a possible allergic pathomechanism. Methods Skin biopsies were taken from red tattoo reactions, graded by conventional microscopy and stained for T and B‐lymphocytes, Langerhans cells, macrophages and tumour necrosis factor (TNF)‐α. Results The study included 19 biopsies from 19 patients. The culprit colours were red/pink (n = 15) and purple/bordeaux (n = 4). Interface dermatitis was clearly the lead pathology found in 78% of samples, overlapped with granulomatous (in 32%) and pseudolymphomatous reaction patterns (in 32%). Epidermal hyperkeratosis (in 89%) was common as was leakage of red pigment across the dermo‐epidermal junction, with transepidermal elimination (in 28%). The dermal cellular infiltration was dominated by T‐lymphocytes (in 100%), Langerhans cells (in 95%) and macrophages (in 100%). TNF‐α was common. Conclusion The predominant histological pattern of chronic tattoo reactions in red/red nuances is interface dermatitis. T‐lymphocytes and Langerhans cells are increased suggesting an allergic pathomechanism. TNF‐α may contribute to reactions. In many cases, overlapping reactive patterns were identified.